Penerapan Komunikasi Terapeutik Terhadap Tingkat Kepuasan pasien - Chichi Hafifa Transyah; Erni Musmiler; Intan Rahmadiarni (Jurnal Amanah Kesehatan, 2023)
A preliminary study was conducted in March 2023 in inpatient rooms with 15 patients, 9 people said they were not satisfied with the therapeutic communication of nurses in the room, patients said there were several nurses who when carrying out actions did not explain what would be done. The aim of the research was to determine the relationship between therapeutic communication and the level of satisfaction of patients in Ruang Rawat Inap Agus Salim Tk III Dr. Reksodiwiryo Padang in 2023. This type of research is descriptive analytic using a cross sectional design. The research was conducted from March to August 2023. The population in this study was 60, the entire population was used as a sample (total sampling). Data were analyzed univariately and bivariately. The results of the univariate research showed that almost half 25 (41.7%) of the patients said therapeutic communication had not been implemented and almost half 20 (33.3%) patients felt dissatisfied. The results of the bivariate research showed a significant relationship between the application of therapeutic communication and the level of patient satisfaction in the Inpatient Room with p-value = 0.000. The research conclusion is that there is a meaningful relationship between the application of therapeutic communication and the level of patient satisfaction. It is recommended for the hospital to refresh nurses regarding the application of communication to increase patient satisfaction with nursing care in the hospital.